A synthesis of mathematics writing: Assessments, interventions, and surveys - Powell, Sarah R.; Hebert, Michael A.; Cohen, Jeremy A.; Casa, Tutita M.; Firmender, Janine M. (Journal of Writing Research, 2017)
Mathematics standards in the United States describe communication as an essential part of mathematics. One outlet for communication is writing. To understand the mathematics writing of students, we conducted a synthesis to evaluate empirical research about mathematics writing. We identified 29 studies that included a mathematics-writing assessment, intervention, or survey for students in 1st through 12th grade. All studies were published between 1991 and 2015. The majority of assessments required students to write explanations to mathematical problems, and fewer than half scored student responses according to a rubric. Approximately half of the interventions involved the use of mathematics journals as an outlet for mathematics writing. Few intervention studies provided explicit direction on how to write in mathematics, and a small number of investigations provided statistical evidence of intervention efficacy. From the surveys, the majority of students expressed enjoyment when writing in mathematics settings but teachers reported using mathematics writing rarely. Across studies, findings indicate mathematics writing is used for a variety of purposes, but the quality of the studies is variable and more empirical research is needed.